The Effect of Murottal Therapy of Surah Ar-Rahman on the Hemodynamic Status of Patients Receiving Intensive Care in the ICU - Kristin Widyowati; Silviana Damayanti; Lailatul Chodiriyah; Mohammad Alif Agus; Wajihatin Zuhroh; Vira Aulia Aviari; Diah Priyantini; Indarti Indarti (Indonesian Academia Health Sciences Journal, 2026)
Introduction : ICU is a unit of care for patients with life-threatening chronic diseases that require ongoing care, monitoring, and the use of life-saving support equipment and drugs. Critical patients who can be treated in the ICU are divided into several criteria, where for the first category or criteria patients treated in the ICU are critical patients with conditions and hemodynamics that are unstable, requiring intensive care and tetritation. Hemodynamic instability is a problem that often occurs in critical patients, because the control mechanisms do not function normally. The high stressor in the ICU room causes the patient's hemodynamics to become unstable. Therefore, it is necessary to carry out non-pharmacological measures to complement the pharmacological therapy that has been given to control hemodynamic status. Non-pharmacological action that can be done is Murrotal therapy. Where murotal therapy can stimulate the hypothalamus to release endorphins so that patients become relaxed and calm and increase parasympathetic nerves. Objective: To analyze the effect of Surah Ar-Rahman murottal therapy on the hemodynamic status of patients in intensive care in the ICU. This research method uses a descriptive method with a case report approach. The population in this study were 1 patient in the ICU RSU HAJI Surabaya. The sample technique used was purposive sampling technique, with the object under study determined based on the criteria the researcher wanted by applying inclusion and exclusion criteria. The independent variable in this study was the administration of Surah Ar-Rahman murottal therapy and the dependent variable in this study was the patient's hemodynamic status. Results: Based on the results of the study, it was found that Murottal therapy in patients in the Intensive Care Unit was effective in stabilizing the patient's hemodynamics. Murottal Al-Qur'an therapy is one of the interventions that can be implemented by nurses to help stabilize the patient's hemodynamics in the ICU room.